2016
DOI: 10.1371/journal.pntd.0004285
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi Experimental Infection Impacts on the Thymic Regulatory T Cell Compartment

Abstract: The dynamics of regulatory T cells in the course of Trypanosoma cruzi infection is still debated. We previously demonstrated that acute murine T. cruzi infection results in an impaired peripheral CD4+Foxp3+ T cell differentiation due to the acquisition of an abnormal Th1-like phenotype and altered functional features, negatively impacting on the course of infection. Moreover, T. cruzi infection induces an intense thymic atrophy. As known, the thymus is the primary lymphoid organ in which thymic-derived regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 53 publications
2
19
0
1
Order By: Relevance
“…This study demonstrated a significant increase in number of cells positive for the transcriptional factor Foxp3 in the CD4 SP compartment during the acute infection. In contrast, architectural restoration of the thymus and an increase in the number of tTreg cells were observed during the course of chronic infection (González et al 2016). Severe ATI was observed to be a primary event along with an overall 80% loss of DP T cells on the 14th day after experimental infection to induce Chagas disease.…”
Section: Parasitic Infections and Atimentioning
confidence: 89%
See 1 more Smart Citation
“…This study demonstrated a significant increase in number of cells positive for the transcriptional factor Foxp3 in the CD4 SP compartment during the acute infection. In contrast, architectural restoration of the thymus and an increase in the number of tTreg cells were observed during the course of chronic infection (González et al 2016). Severe ATI was observed to be a primary event along with an overall 80% loss of DP T cells on the 14th day after experimental infection to induce Chagas disease.…”
Section: Parasitic Infections and Atimentioning
confidence: 89%
“…Increasing prolactin secretion as induced by the administration of metoclopramide, a D2-dopaminergic antagonistic drug 2. Treatment with fingolimod (FTY720), an antagonist of S1P receptor González et al 2016;Lepletier et al 2012Lepletier et al , 2013Lepletier et al , 2014Pérez et al 2012 Plasmodium berghei, P. yoelii and P. berghei ANKA 1. Matrix metalloproteinases (MMPs), i.e., MMP-2 and MMP-9…”
Section: Pathogenic Infections and Ati Viral Infections And Atimentioning
confidence: 99%
“…Данные молекулы отвечают как за миграцию клеток в тимус, так и за индукцию Treg на периферии. Показано, что стимуляция TLR на ДК продуктами микробного происхождения подавляет экспрессию указанных молекул и, следовательно, ингибирует их миграцию в тимус и снижает их способность индуцировать супрессорные клетки [15,17]. В принципе, не очень понятна роль данного механизма в развитии инфекционного процесса.…”
Section: процессы формирования центральной «инфекционной» толерантноunclassified
“…Trypanosoma cruzi is the causative agent of Chagas' disease, a neglected condition [1] . The parasite is transmitted to humans by infected bugs [2] .…”
Section: Introductionmentioning
confidence: 99%